IMPACTS OF ARTISANAL GOLD MINING AND EFFORTS TO MINIMIZE NEGATIVE IMPACTS TO THE ENVIRONMENT - HUSAINI HUSAINI; LILI TAHLI; MUTA’ALIM MUTA’ALIM (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2012)
Indonesia has extensive primary and secondary gold ore deposits that are scattered at several islands. The processing method for gold includes cyanidation, amalgamation and gravity concentration. Amalgamation is one of the most dangerous methods that pollutes the environment. The process is conducted by artisanal gold mining extensively throughout the country and involving around 100.000 miners. The process is started by crushing the ore up to 2-3 cm, then put in the trommel along with Hg and water. The trommel is then rotated for 4-5 hours to produce amalgam (Au-Hg) to be separated from its tailing by panning. The clean Au-Hg, mixed with liquid Hg, is then squeezed to separate the Hg excess. The Au-Hg, mixed with borax is then burnt in a crucible to evaporate its Hg and get the golds bullion (Au-Ag metal). The gold is obtained after the silver within the bullion is leached by HNO3 equipment used for burning the Au-Hg is an open vessel that is operated in the kitchen at which the people also cook the food. This condition is very dangerous for the miner and their families as the Hg vapor is very toxic and can damage human lung. Another problem is that Hg-containing fine tailings are directly discharged to the river. This mercury can pollute the aquatic system and become dangerous for human through food chain. The efforts decreasing the negative effect of artisanal mining employ a retort to burn the amalgam, centralize the trommels; concentrate the gold ores prior to amalgamation. Jig, shaking table, sluice box can be used for upgrading the gold. If tailing with relatively high gold content would be processed by gravity concentration or cyanidation, the location for tailing gold processing should be safe and far from the river and houses.